Impact of polarized polychromatic incoherent light upon bioradical parameters of rat tissues and blood serum - Khmil, N. V.; Ovsyannikova, T. M.; Chaykovskaya, N. V.; Podoprigorova, V. G. (Biophysical Bulletin, 1970)
The effect of a seven-day exposure of rats in vivo of polarized polychromatic noncoherent light (PPL) on oxidative-antioxidant parameters in blood serum and tissues (skin, liver, heart) and morphological structure of these tissues. The development of systemic bioradical imbalance in liver and heart, and also in skin through degradation of the basement membrane was revealed.